The Contact Allergen Methylisothiazolinone (MIT) is a Potent Activator of the TRPA1 Ion Channel - Ilari Mäki‐Opas; Samu Luostarinen; Mari Hämäläinen; Katsuhiko Muraki; Eeva Moilanen (Pharmacology Research & Perspectives)
ABSTRACT Methylisothiazolinone (MIT) is a known inducer of allergic contact dermatitis that is used as a preservative and a biocide in consumer products. Transient receptor potential ankyrin 1 (TRPA1) is a non‐selective cation channel expressed in neurons and in some nonneuronal cells including keratinocytes. In neurons, TRPA1 mediates itch, pain and neurogenic inflammation. It has also been shown that TRPA1‐deficient animals have reduced expression of inflammatory cytokines in experimental models of allergic contact dermatitis. Therefore, we aimed to test the hypothesis that TRPA1 is activated by MIT and mediates MIT‐induced inflammatory conditions. In Fluo 3‐AM intracellular Ca2+ measurements MIT caused a dose‐dependent increase in the intracellular calcium which was inhibited with the TRPA1‐antagonist A‐967079. In whole‐cell patch clamp recordings, MIT was confirmed to induce currents blocked by A‐967079. EC50 values were 2.17 μM at +70 mV and 6.28 μM at −70 mV in Ca2+‐free conditions. Mutation of the cysteine 621 in TRPA1 lowered the potency of MIT to activate the channel. In the mouse model of MIT‐induced acute inflammatory paw edema, mice treated with a TRPA1 antagonist as well as TRPA1‐deficient mice had reduced edema formation. In addition, TRPA1‐deficient mice sensitized to MIT had reduced elevation of IL‐4 expression in skin following exposure to MIT when compared to wild‐type mice. In conclusion, we report here, for the first time, that the preservative and known contact sensitizer MIT is a potent agonist of TRPA1 and that TRPA1 mediates some of the effects of MIT in inflammatory conditions. These results together with the previous findings suggest that TRPA1 is a factor in the pathogenesis of type 2 T‐helper cell (Th2)‐skewed contact allergy and as such a potential drug target to treat Th2‐driven diseases.